Mobile Phone Security and Forensics A Practical Approach - Androulidakis, Iosif I.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This new edition provides both theoretical and practical background of security and forensics for mobile phones. The author discusses confidentiality, integrity, and availability threats in mobile telephones to provide background for the rest of the book. Security and secrets of mobile phones are discussed including software and hardware interception, fraud and other malicious techniques used "against" users. The purpose of this book is to raise user awareness in regards to security and privacy threats present in the use of mobile phones while readers will also learn where forensics data reside in the mobile phone and the network and how to conduct a relevant analysis. The information on denial of service attacks has been thoroughly updated for the new edition. Also, a major addition to this edition is a section discussing software defined radio and open source tools for mobile phones.
Introduction: Confidentiality, Integrity, and Availability Threats in Mobile Phones -- A Multinational Survey on User's Practices, Perceptions, and Awareness Regarding Mobile Phone Security -- Voice, SMS, and Identification Data Interception in GSM -- Software and Hardware Mobile Phone Tricks -- SMS Security Issues -- Mobile Phone Forensics -- Conclusion.
Keywords: Telecommunication; Data protection; Security systems; Forensic sciences; Communications Engineering, Networks; Data and Information Security; Security Science and Technology; Forensic Science